2005
DOI: 10.1128/jcm.43.4.1617-1624.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Determined on the Basis of katG463 and gyrA95 Polymorphisms, Spoligotyping, and IS 6110 Typing, of Mycobacterium tuberculosis Complex Isolates from Italy

Abstract: Mycobacterium tuberculosis complex isolates (n ‫؍‬ 248) collected during a 1-year period in Tuscany, Italy, were genotyped for the katG463 and gyrA95 polymorphisms and by standard spacer oligonucleotide typing (spoligotyping) and IS6110 restriction fragment length polymorphism (RFLP) assays. Most of the isolates (n ‫؍‬ 212; 85.5%) belonged to genotypic groups 2 and 3, which included most isolates from Italian-born patients. The remaining isolates were genotypic group 1 organisms, which were prevalent among for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…Our results showed that the T clade comprised the majority of SCG-6a and -6b, but it could also be found in SCG-3abc, -4, and -5, suggesting that the T clade classification in fact includes a number of phylogenetically distinct subgroups. The Haarlem (H) clade is another spoligotype group that occurs at high frequency in human tuberculosis studies (20,44). Our results showed that the H clade could be found in two distinct genetic clusters, SCG-3b and SCG-5, although neither of these SCGs contained only H clade isolates.…”
Section: Geographic Distribution Of Snp Clustersmentioning
confidence: 67%
“…Our results showed that the T clade comprised the majority of SCG-6a and -6b, but it could also be found in SCG-3abc, -4, and -5, suggesting that the T clade classification in fact includes a number of phylogenetically distinct subgroups. The Haarlem (H) clade is another spoligotype group that occurs at high frequency in human tuberculosis studies (20,44). Our results showed that the H clade could be found in two distinct genetic clusters, SCG-3b and SCG-5, although neither of these SCGs contained only H clade isolates.…”
Section: Geographic Distribution Of Snp Clustersmentioning
confidence: 67%
“…Among these, the predominant spoligotypes, shown in Table 2, include (i) ST53, with a total of 98 isolates, a ubiquitous spoligotype belonging to clade T1; (ii) ST1, with 48 isolates, which represents the predominant spoligotype of the Beijing family; (iii) ST50, ST47, and ST62, belonging to the Haarlem family, with 43, 30, and 22 isolates, respectively; and (iv) ST42 of the LAM9 clade, with 35 isolates. Among the other clustered major spoligotypes, it is worthwhile to mention the occurrence of spoligotype ST1737, clade T1 Tuscany, with 10 isolates which likely represent autochthonous spoligotypes, as previously reported (20), or of spoligotypes which are endemic in distant geographical areas, such as ST26 of the CAS1_Delhi clade, with 11 isolates; ST19 of the EAI2_Manilla clade, with 10 isolates; and ST181 of the Africanum type 1 clade, with 5 isolates. Among the remaining 213 (25.7%) unclustered isolates, 99 (11.9%) were not yet reported to the SpolDB4 database and represented the true orphan isolates, indicated with ST0; the remaining 114 (13.8%) unclustered isolates, though unique, were already reported in SpolDB4, which allowed the attribution of an ST number.…”
Section: Epidemiologicalmentioning
confidence: 99%
“…Spoligotyping identified 11 genotype families, namely, LAM3/F11 (n ϭ 86), W-Beijing (n ϭ 70), X (European low-copy-number family by IS6110-based restriction fragment length polymorphism analysis; n ϭ 30), S/F28 (n ϭ 21), Zimbabwean (n ϭ 7), other LAM (n ϭ 8), Tuscany and Russian (n ϭ 12) (Brudley et al, unpublished), Haarlem (n ϭ 11), T clade (n ϭ 20), CAS (n ϭ 5) and "unknown" clades (n ϭ 15) (4,8).…”
mentioning
confidence: 99%